Pengaruh Karakteristik Perbankan Syariah dan Peraturan Bank Indonesia Nomor: 13/9/PBI/2011 Terhadap Profitabilitas Perbankan Syariah di Indonesia - Denas Hasman Nugraha, (SALIHA: Jurnal Pendidikan & Agama Islam, 2018)
The banking industry plays an important role for economic development as a Financial Intermediary or intermediary parties excess funds to those who need the funds in accordance with the Law of the Republic of Indonesia No. 10 of 1998 on banking. Therefore, we need a special provision governing the implementation of the Restructuring Financing for the Bank (Bank Indonesia Regulation No. 10/18 / PBI / 2008). The purpose of this study is to analyze empirically the influence of internal conditions / characteristics banking (FDR, CAR, ROA and NPF), firm size (SIZE) and Bank Indonesia Regulation No. 13/9 / PBI / 2011 (PBI) to the profitability of Islamic banking in Indonesia. Data analysis method used in this research is panel data regression analysis (pooled data) financial data of Islamic banking in Indonesia. The research sample with the criteria of Islamic Banks that have data quarterly financial statements in the period September 2010 (Q3) -June 2015 (Q2). The results showed that the FDR variables obtained significant effect on ROA (-) but no effect on ROE and NPM. NPF variable test results obtained influence on ROA (-), ROE (-) and NPM (-). CAR variable test results obtained significant effect on ROA (-) and ROE (-) but did not affect the NPM. The test results obtained BOPO variables significantly influence the NPM (-) but no effect on ROA and ROE. SIZE variable test results obtained significant effect on ROA (-) but no effect on ROE and NPM. The test results obtained PBI variables significantly influence the ROE (-) but no effect on ROA and NPM.